The Discourse of Postmemory of Grand Watudodol Underwater Posbox Advertisement - Akbar, Syaiful; Tallapessy, Albert; Hari Murti, Ghanesya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This paper examines the discourse of postmemory in the promotional media of Grand Watudodol Underwater Posbox tourist attraction, Banyuwangi, Indonesia. This is qualitative research. The data were cdollected from Instagram posts taken from the official accounts of Banyuwangi tourism, bwi.id, and posindonesia.ig. The collected data wer analysed using multimodal discourse analysis. To restore the tourism sector affected by the pandemic, the Banyuwangi government has built new tours in various areas. Among them is one that collaborates with Pos Indonesia, called Posbox Underwater, which is located on Grand Watudodol (GWD) beach. This tour offers diving activities and traumatic events when sending letters. Traumatic events in this context come from the Millennial generation. For example, they must find proper paper, buy stamps, and go to the nearest post office, all of which are quite a hassle. Not to mention the worry about the letter not being delivered, the recipient not replying, making the writer curious about their response, and the time required. This research uses Gunther Kress & van Leeuewen's visual grammar design, McCabe's thematic progression, and Mariane Hirsch's postmemory to find the discourse in the existing promotional media. It is found that the transmission of trauma is depicted visually. However, textually, persuasive discourse is found in the caption. In addition, visitor testimonials also confirmed that the postmemory discourse was indeed transmitted affiliative. It can be concluded that multimodal becomes a means to advertise postmemory discourse.